2006
DOI: 10.1017/s0263034606060678
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms in spectroscopic diagnostics of hot dense plasmas

Abstract: This paper will present a novel genetic-algorithm-based code~GASPED!, developed for the analysis of fine features e.g., satellite structure and line shifts! in X-ray spectra emitted by hot dense plasmas. The problem dependent modification of standard genetic-algorithm concepts allows efficient decomposition of spectra in concrete physical terms, such as resonance and intercombination lines, dielectronic satellites, or prospective nuclear transitions. Two examples of the code application demonstrate the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The experimental data presented in figure 14 shows clearly that the satellite emission is even more intense that the He β line. The spectrum decomposition performed using a genetic algorithm (GA) code [41] complemented by an input from theoretical simulations depicted in figure 15 provides an excellent fit to the data.…”
Section: Exotic X-ray Emission In Dense Laser Produced Plasmasmentioning
confidence: 99%
“…The experimental data presented in figure 14 shows clearly that the satellite emission is even more intense that the He β line. The spectrum decomposition performed using a genetic algorithm (GA) code [41] complemented by an input from theoretical simulations depicted in figure 15 provides an excellent fit to the data.…”
Section: Exotic X-ray Emission In Dense Laser Produced Plasmasmentioning
confidence: 99%
“…The solutions are then evaluated using a fitness function that assigns a number to each solution [34]. Genetic algorithms have found use in various problems regarding radiation spectroscopy such as: analysis of gamma-ray spectra [6]- [9], analysis of coincidence spectra [35], decomposition of multiple hit events in gamma-ray tracking detectors [36], x-ray spectroscopy diagnostics for hot plasmas [37], and analysis of neutron spectra [38]. A generic block diagram of a genetic algorithm is presented in Fig.…”
Section: B Elements Of Genetic Algorithmsmentioning
confidence: 99%
“…The composite profile shown in Fig. 4 was analyzed using a problem-dependent genetic algorithm code GASPED [12]. Repeated GASPED runs demonstrated that the whole spectrum can be well fitted by seven pseudo-Voigt profiles.…”
Section: Plasma-induced Spectral Line Shiftsmentioning
confidence: 99%